FINANCIAL LITERACY AND FINANCIAL INCLUSION AS COMPONENTS OF PUBLIC GOVERNANCE IN THE DEVELOPMENT OF UKRAINE’S BANKING SYSTEM: THE EXPERIENCE OF LEADING COUNTRIES - Iermak, Valerii (Public Management and Policy, 2025)
In the current context of global instability, growing cyber threats, and recurring financial and economic crises that erode trust in financial institutions, leading countries are increasingly adopting a strategic approach to the development of national financial literacy policies. This issue has gained particular relevance about ensuring financial inclusion as a key mechanism for engaging citizens with the banking system and the financial market at large. Despite some progress, Ukraine still lacks an integrated institutional framework for managing the development of financial literacy, which significantly limits the country’s ability to build and implement a comprehensive strategy in this field. The purpose of this study is to analyze international experience in the implementation of public policy on financial literacy and to identify the most effective governance practices that could be adapted to the Ukrainian context to foster the development of the banking system through enhanced financial inclusion. As a result of the comparative analysis of strategies in Germany, Ireland, and Austria, it has been found that the key factors of effective financial policy implementation include a multi-level institutional management structure, interdepartmental coordination, targeted financing, systematic monitoring, and the digitalization of educational processes. The most successful countries ensure strong cooperation between public, private, and non-profit actors and operate based on legally enshrined national strategies with clearly defined action plans. At the same time, some challenges remain, such as unequal access to financial education among specific population groups, including youth, the elderly, and migrants. The analysis confirms the urgent need for a coherent state policy on financial literacy development in Ukraine, grounded in the best European practices. It is argued that the introduction of a multi-level coordination model based on public-civil society partnership can foster a higher level of financial awareness among citizens, strengthen financial inclusion, and increase the resilience of the banking system. This research may serve as a foundation for further scientific exploration focused on developing a concrete institutional mechanism for implementing a national financial education strategy in Ukraine.